Processes of National Identification in Migrant Population: Continuities and Breakdowns in Intergenerational Relation - Novaro, Gabriela (Revista de Antropología Social, 2014)
This work intends to contribute to the study of migrations, education and processess of identification, based on the developments of a research with migrant Bolivian population that lives in a locality near to the city of Buenos Aires. In the article I focus on the educational expectations and the formative experiences of families and associations of a neighborhood, and their bonds with local schools. I analyze the way in which adults transmit simultaneously the mandate of maintaining Bolivia as an important reference of identification and the expectation of their inclusion into the new society. I focus also in schooling experiences, pointing the tensions between the new discourses of inter-culturality, and the fact that Bolivian children, and sons and daughters of Bolivian parents are frequently understood as foreigners from a traditional nationalistic speech, which includes strong stereotypes about their original country.
Keywords: Migration; Childhood; Identity Processess; Knowledges; Schooling.